TINJAUAN PERLINDUNGAN HUKUM TERHADAP ASURANSI PENDIDIKAN BAGI ANAK ASN: URGENSI REFORMULASI REGULASI NEGARA - Muthahir, Ardi (Law Journal (LAJOUR), 2025)
Legal protection in the form of education insurance for children of the State Civil Apparatus (ASN) in Indonesia still faces various problems in regulation and implementation. This study aims to analyze the urgency of regulatory clarity related to educatio n insurance for ASN children, as well as compare it with similar schemes in developed countries such as Japan and Australia. The research method uses a normative juridical approach with qualitative descriptive analysis techniques. The results of the study show that the legal provisions governing educational scholarships for ASN children in Indonesia have not met the principles of justice and maximum protection. Existing policies, such as scholarship assistance in Government Regulation Number 70 of 2015 and Government Regulation Number 102 of 2015, are still limited, not comprehensive, and do not cover all the educational needs of ASN children on an ongoing basis. In comparison, the Mutual Aid Association system in Japan and the Commonwealth Superannuation Sc heme in Australia show a more mature and sustainable model of education protection with the support of government contributions. Special regulations and active participation of the state are needed to present an education insurance program that guarantees the future of ASN children's education as a whole